The dignity of the human person as grounds for granting medicines by the Supreme Court (Revista do Tribunal Regional Federal da 3ª Região, 2016)
In the last decade, the Federal Supreme Court (STF) has been called upon more frequently to rule on cases where the state refuses to supply medicines. Considering that, in addition to the right to life and health, the STF has used the dignity of the human person as a basis for granting medicines, this article aims to discuss this basis. The dignity of the human person is considered to be an absolute value and cannot be overridden at any time or in any circumstance - unlike other values which, embodied in the Federal Constitution by means of principles, can be weighed against other principles of greater relevance in a specific case. This article aims to understand the meaning of invoking the dignity of the human person as a foundation in cases where medicines are granted, and having considered the hypothesis that its use goes beyond invoking the right to life and health in cases where medicines are provided.
Keywords: dignity of the human person; health; provision of medicines; STF